Implementing the Flipped Classroom Approach in the Teaching Process - Fedorová Andrea (Acta Educationis Generalis)
This study explores the application of the flipped classroom approach in teaching professional English to Civil Engineering students at the Technical University of Košice. This pedagogical shift aims to improve language proficiency, engagement, and critical thinking.